Super-enhancers in immune system regulation: mechanisms, pathological reprogramming, and therapeutic opportunities - Lai, Xin; Li, Caizhi; Tang, Xinglinzi; Luo, Xinyi; Wu, Feiyan; Liang, Yuhong; Huang, Bihui; Li, Hang (Frontiers in Immunology, 2025)
Super-enhancers (SEs) are dynamic chromatin structures that function as epigenetic hubs, orchestrating cell-type-specific transcriptional programs crucial for immune cell differentiation, functional specialization, and adaptive responses. These enhancer clusters integrate transcription factor (TF) networks, chromatin-modifying signals, and three-dimensional genome organization to govern lineage commitment, effector function acquisition, and metabolic reprogramming while enabling plasticity in response to environmental cues. SEs exhibit spatiotemporal regulatory properties, such as chromatin looping, phase-separated condensate formation, and stimulus-driven enhancer-promoter rewiring, all of which stabilize transcriptional outputs vital for immune homeostasis. Pathological dysregulation of SEs disrupts immune tolerance and amplifies aberrant transcriptional circuits, contributing to immune-mediated diseases marked by chronic inflammation, autoimmunity, or malignancy. Emerging therapeutic strategies targeting SE-associated components show promise in dismantling pathogenic enhancer networks through CRISPR-based editing, small-molecule inhibitors, and proteolysis-targeting chimeras(PROTACs). However, challenges remain in achieving therapeutic specificity amidst the dynamic reorganization of SEs and ensuring cell-type-selective delivery. By providing insights into SE-driven chromatin dynamics and transcriptional control in health and disease, this review focuses on two central questions: whether SEs causally drive immune cell fate decisions, and how they function within shared core transcriptional regulatory networks across cancer, infection, and autoimmune diseases. Future advances in multi-omics profiling, single-cell resolution analyses, and combinatorial therapeutic strategies will be critical for translating SE biology into precision interventions that restore immune equilibrium in dysregulated conditions.